Non-HIV Pneumocystis pneumonia: do conventional community-acquired pneumonia guidelines under estimate its severity? - Asai Nobuhiro; Motojima Shinji; Ohkuni Yoshihiro; Matsunuma Ryo; Nakasima Kei; Iwasaki Takuya; Nakashita Tamao; Otsuka Yoshihito; Kaneko Norihiro (Multidisciplinary Respiratory Medicine, 2012)
Abstract Background Non-HIV Pneumocystis pneumonia (PCP) can occur in immunosuppressed patients having malignancy or on immunosuppressive agents. To classify severity, the A-DROP scale proposed by the Japanese Respiratory Society (JRS), the CURB-65 score of the British Respiratory Society (BTS) and the Pneumonia Severity Index (PSI) of the Infectious Diseases Society of America (IDSA) are widely used in patients with community-acquired pneumonia (CAP) in Japan. To evaluate how correctly these conventional prognostic guidelines for CAP reflect the severity of non-HIV PCP, we retrospectively analyzed 21 patients with non-HIV PCP. Methods A total of 21 patients were diagnosed by conventional staining and polymerase chain reaction (PCR) for respiratory samples with chest x-ray and computed tomography (CT) findings. We compared the severity of 21 patients with PCP classified by A-DROP, CURB-65, and PSI. Also, patients’ characteristics, clinical pictures, laboratory results at first visit or admission and intervals from diagnosis to start of specific-PCP therapy were evaluated in both survivor and non-survivor groups. Results Based on A-DROP, 18 patients were classified as mild or moderate; respiratory failure developed in 15 of these 18 (83.3%), and 7/15 (46.7%) died. Based on CURB-65, 19 patients were classified as mild or moderate; respiratory failure developed in 16/19 (84.2%), and 8 of the 16 (50%) died. In contrast, PSI classified 14 as severe or extremely severe; all of the 14 (100%) developed respiratory failure and 8/14 (57.1%) died. There were no significant differences in laboratory results in these groups. The time between the initial visit and diagnosis, and the time between the initial visit and starting of specific-PCP therapy were statistically shorter in the survivor group than in the non-survivor group. Conclusions Conventional prognostic guidelines for CAP could underestimate the severity of non-HIV PCP, resulting in a therapeutic delay resulting in high mortality. The most important factor to improve the mortality of non-HIV PCP is early diagnosis and starting of specific-PCP therapy as soon as possible.